PTH-005 Laparoscopy-assisted Ercp Following Bariatric Gastric Bypass Surgery: Initial Experience At A Uk Tertiary Referral Centre. (9th June 2014) - Paranandi, B; Joshi, D; Mohammadi, B; Read, S; Adamo, M; Webster, GJ
Abstract : Introduction: Bariatric gastric bypass surgery is being increasingly performed, but ERCP in these patients poses a unique challenge because of lack of per-oral access to the stomach. Small series suggest a higher technical success rate, using Laparoscopy assisted ERCP (LA-ERCP), than with an enterosocpic approach via the Roux-en-Y anastamosis. We present the experience thus far of LA-ERCP at our UK tertiary referral Pancreaticobiliary unit. Methods: Retrospective case series of consecutive patients undergoing LA-ERCP in our unit between September 2011 and June 2013. Data was retrieved from electronic, clinical and endoscopy records. Results: All LA-ERCP procedures were undertaken in the operating theatre with a mobile endoscopy stack and Olympus TJF duodenoscopes equipped with standard ERCP accessories. The laparoscopic procedure involved formation of a closed pneumoperitoneum to a pressure of 12 mmHg with a Veress needle. A 15 mm trocar was placed in the epigastrium and two 5mm trocars were placed in the right and left flanks for surgical access. A 15 mm gastrostomy port was secured with purse-string sutures. The duodenoscope was inserted via the port into the gastric remnant and advanced conventionally into the duodenum. Standard therapeutic ERCP technique was then performed. Closure of the gastrostomy was achieved with a double layer of 2–0 vicryl sutures. Peri-procedural prophylactic intravenous antibiotics were administered routinely in all patients. Conclusion: Five LA-ERCPs (on 5 patients) were performed. All patients were Female with median age 44 years (range 36–71). Indications included symptomatic bile duct stones (3/5), benign papillary fibrosis (1/5) and retained biliary stent (1/5). Duodenal access, biliary cannulation and completion of therapeutic aim were achieved in all patients. 4/5 (80%) patients required endoscopic sphincterotomy. The 5th patient had a prior sphincterotomy. The mean duration of procedures was approximately 94 min (range 70–135). Median post-op length of stay was 2 days (range 1–9). One patient developed mild post-procedural acute pancreatitis. Otherwise no procedure related complications were seen. Reference: Our early experience of LA-ERCP is that it is safe and effective. The technique may require particular consideration, as bariatric surgery is increasingly performed, in a patient group at significant risk of bile duct stones. Disclosure of Interest: None Declared.